Effectiveness of Pregnancy Exercises in Reducing Lower Back Pain Among Third Trimester Pregnant Women - Putu Rosita Saraswati; Ni Wayan Suarniti; Sri Rahayu (Media Keperawatan Indonesia, 2024)
Lower back pain is one of the most common complaints experienced by pregnant women, particularly in the third trimester. Pregnancy exercise is an effective intervention to alleviate this discomfort. This study aimed to evaluate the differences in lower back pain levels before and after pregnancy exercise in third-trimester pregnant women at UPTD Klungkung I Community Health Center. A quasi-experimental design with a one-group pretest-posttest approach was utilized, involving 21 third-trimester pregnant women selected through purposive sampling. Data were collected using the Numerical Rating Scale (NRS) and analyzed with the Wilcoxon test following the Shapiro-Wilk normality test. The results showed a mean lower back pain score of 7.14 (SD = 0.793) before the intervention, with a significant reduction after pregnancy exercises (p < 0.001). These findings indicate a substantial improvement in lower back pain among participants after pregnancy exercises. It is recommended that pregnant women actively engage in pregnancy exercise programs to enhance comfort during pregnancy and alleviate back pain complaints.